Money and Credit: Lessons of the Irish Bank Strike of 1970 - Malte Krueger (Credit and Capital Markets – Kredit und Kapital, 2018)
In Ireland, there was a bank strike that led to a complete shut-down of the main part of the banking system from May to November 1970. The effects of this strike were surprisingly limited. This had led some observers to conclude that trade credit can easily substitute for bank deposits as a means of payment. In this paper, it is shown how cash and cheques were used as substitutes and complements allowing for "business as usual" for an extended period of time. This paper argues that such a situation would not have prevailed much longer. The lack of a proper settlement mechanism implied that risks were rising for almost all transactors. In order to contain risks the use of trade credit would have declined and economic performance would have deteriorated progressively. – – In Irland hat 1970 ein Streik der Bankangestellten dazu geführt, dass wesentliche Teile des Banksystems von Mai bis November geschlossen waren. Die Auswirkungen dieses Streiks waren erstaunlich gering. Dies hat einige Beobachter zu der Schlussfolgerung veranlasst, dass Bankeinlagen als Zahlungsmittel sehr leicht durch Handelskredit ersetzbar sind. In dem vorliegenden Beitrag wird gezeigt, wie Bargeld und Schecks sowohl als Substitute als auch als Komplemente einen weitgehend störungsfreien Fortgang des geschäftlichen Lebens ermöglicht haben. Es wird jedoch argumentiert, dass dieser Zustand nicht sehr viel länger Bestand gehabt hätte. Ohne die Verfügbarkeit eines Settlement-Mediums nahmen die Risiken aller am Wirtschaftsleben Beteiligten ständig zu. Im Laufe der Zeit hätte die Vergabe von Handelskredit zunehmend eingeschränkt werden müssen, um diese Risiken zu begrenzen. Eine solche Einschränkung hätte die wirtschaftliche Aktivität zunehmend belastet.
Keywords: N14; E02; E59; G21; 330; money; banking; payments; clearing&settlement; Ireland; trade credit